2013
DOI: 10.2131/jts.38.503
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and reactive oxygen species production induced by magnetite nanoparticles in mammalian cells

Abstract: -We examined the genotoxicity of magnetite nanoparticles (primary particle size: 10 nm) on human A549 and Chinese hamster ovary (CHO) AA8 cells. Six hours' treatment with the particles dose-dependently increased the frequency of micronuclei (MN) in the A549 and CHO AA8 cells up to 5.2% and 5.0% at a dose of 200 μg/ml (34 μg/cm 2 ), respectively. In A549 cells, treatment with the nanoparticles (2 μg/ml) for 1 hr induced H2AX phosphorylation, which is suggestive of DNA double strand breaks (DSB). Treating CHO AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…IONPs produce free radical species that reduce the levels of cellular antioxidants significantly, which may lead to apoptosis via oxidative damage to intracellular proteins, DNA and increased LPO (Belozerskaia and Gessler, 2007;Ahmad et al, 2010;Naziroglu et al, 2010;Wan et al, 2012). Previous studies by Konczol et al (2011) and Kawanishi et al (2013) have reported ROS generation in A549 and CHO cells treated with magnetite NPs. Current results showed a statistically significant decrease in the GSH content in comparison to control from 24 to 72 h in the IONP-treated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IONPs produce free radical species that reduce the levels of cellular antioxidants significantly, which may lead to apoptosis via oxidative damage to intracellular proteins, DNA and increased LPO (Belozerskaia and Gessler, 2007;Ahmad et al, 2010;Naziroglu et al, 2010;Wan et al, 2012). Previous studies by Konczol et al (2011) and Kawanishi et al (2013) have reported ROS generation in A549 and CHO cells treated with magnetite NPs. Current results showed a statistically significant decrease in the GSH content in comparison to control from 24 to 72 h in the IONP-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Novotna et al () reported that ϒ Fe 2 O 3 increased oxidative stress and led to significant DNA damage. Kawanishi et al () found genotoxic effect of magnetite NPs in A549 and CHO cells. Karlsson et al () and Konczol et al () reported that Fe 2 O 3 and Fe 3 O 4 cause increased DNA migration detected by comet assay in the A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MN test was carried out as previously described (Kawanishi et al, 2013). Briefly, CHO cells (4 × 10 5 cells/dish) were seeded in φ60 mm plastic cell culture dishes one day before the infection procedure.…”
Section: Micronucleus Testmentioning
confidence: 99%
“…Engineered nanomaterials (ENM) are used in various fields of the human environment, and assessment of their safety is, therefore, urgently required. So far, we have examined the genotoxicity of various ENM by using in vitro and in vivo assays, which indicated that inflammatory response, induced by macrophages and other immune cells, is considered a key mechanism for the genotoxicity and other toxic properties of ENM . In general, a single culture of tissue resident cells has been used for in vitro assays to evaluate genotoxicity of ENM.…”
Section: Introductionmentioning
confidence: 99%